Reverse-zoonotic transmission of SARS-CoV-2 lineage alpha (B.1.1.7) to great apes and exotic felids in a zoo in the Czech Republic - Nagy, Alexander; Stará, Martina; Vodička, Roman; Černíková, Lenka; Jiřincová, Helena; Křivda, Vlastimil; Sedlák, Kamil (Archives of virology, 2022)
We report an outbreak of SARS-CoV-2 lineage alpha in gorillas and felid species in a zoo in Prague, Czech Republic. The course of illness and clinical signs are described, as are the results of characterization of these particular SARS-CoV-2 variants by next-generation sequencing and phylogenetic analysis. The putative transmission routes are also discussed.
Keywords: Animals; Česká republika; Felidae; Phylogeny; Hominidae; lidé; zvířata; SARS-CoV-2; fylogeneze; Czech Republic; COVID-19; Humans